Perceived weight stigma and disordered eating behaviors among postpartum women: The mediating role of weight bias internalization and postpartum depression - Jiayuan Peng; Xiangmin Tan; Ni Ning; James Wiley; Nan Hua; Yuan Zeng; Mei Sun (International Journal of Nursing Studies Advances)
Background: Weight stigma is linked to adverse effects, but whether it directly heightens the risk of disordered eating behaviors or psychological factors mediate this connection among postpartum women is uncertain. Objectives: To investigate the relationship between perceived weight stigma and disordered eating behaviors (restrained eating, emotional eating, and external eating) and identify the mediating role of weight bias internalization and postpartum depression (PPD). Methods: This cross-sectional study involved 507 postpartum women. Data were collected anonymously using self-reported questionnaires, including the Perceived Weight Stigma Questionnaire, Weight Bias Internalization Scale, Edinburgh Postpartum Depression Scale, and Dutch Eating Behavior Questionnaire. Data were analyzed using descriptive statistics, Pearson's correlation analysis, hierarchical linear regression, and mediation analysis. Results: The results showed that the relationship between perceived weight stigma and disordered eating behaviors was fully mediated by weight bias internalization and PPD. Specifically, perceived weight stigma was associated with greater weight bias internalization, which was associated with greater PPD, and greater PPD was associated with greater disordered eating behaviors. Conclusion: This may be the first study to propose a chain mediation model exploring the roles of weight bias internalization and PPD in the relationship between perceived weight stigma and disordered eating behaviors among postpartum women. The findings enhance the understanding of the psychological impacts of perinatal weight stigma and underscore the importance of addressing weight stigma in postpartum care. Comprehensive interventions should be developed to enhance postpartum health and reduce the risk of disordered eating behaviors.